Diffusion Model and Empirical Study of the Multi-Generation Products Based on Competition - ZHANG, Lei; LI, Yi-jun; YAN, Xiang-bin (Systems engineering (Amsterdam), 2008)
Diffusion theory, which deals with the market growth rule governing new products, is an important research method in the field of marketing. This study deals with the two subjects as follows: One is the competition-complementarity effect on products of different categories in the process of diffusion, and the other is the competition-substitution effect on products of different generations. With Kim's model, this study indicates that the potential adopters of one product is influenced both by the adopters of different categories, and by the relative product price of different generations of the same category as well. Furthermore, in this article, a multi-generation products model is proposed according to the analysis above and an empirical study is taken on the telecommunication products. The results indicate that the model has a perfect fitness by using the limited historical data, and the parameter estimation results provide complete understanding of telecommunication products diffusion. Moreover, multi-generation products diffusion model is better than other models in terms of forecast accuracy. So, we conclude that the multi-generation products diffusion model based on competition is effective.